The Prevalence of Gestational Diabetes Mellitus and Predisposing Factors among Pregnant Women Attending Antenatal Clinic at Kawolo General Hospital. A Cross-sectional Descriptive Study. - Comfort Ochieng; Kezia Kalembe; Collins Mujjuzi; Anna Nakhabi; Isaac Kakinda; Enoch Muwanguzi; Yona Mbalibulha (Student's Journal of Health Research, 2022)
Background Globally, the prevalence of Hyperglycemia first detected in pregnancy (Gestational Diabetes Mellitus) varies from 1 - 28 %. 16.2 % of women have some form of hyperglycemia, of which GDM is about 85.1%.  87.6% of GDM accounts are in low- and middle-income countries. Hyperglycemia in pregnancy is estimated to affect 21.4 million (16.9%) live births, with GDM accounting for 16% of these cases. In Kawolo General Hospital, pregnant women aren't screened for blood glucose during antenatal visits, thus the need and relevance of investigating GDM, according to WHO recommendations. Methodology: A total of 334 participants were recruited by systematic random sampling. Blood and urine samples were collected.  RBS, OGTT, and urine glucose tests were done. Data were analyzed using STATA version 13 to determine the prevalence and association between the risk factors of GDM among the respondents. Results The study revealed the prevalence of GDM as 4.5%.  Hypertension and elevated blood pressure were significantly associated with GDM, with p values of 0.00 and 0.01 respectively among women of various ages, gravida, and trimester. The majority of the participants were aged 18 to 25 years (58.7%). over 86.5% were married. 56.9% had secondary education. (38.9%) were unemployed. (34.4%) were Catholics. (46.1%) had normal body mass index with an average body weight of 65 kg and 160cm (height). 70.6% had normal blood pressure. 21.56% had elevated blood pressure. (56.6%) had their protein uptake. Vitamins (100%) were high, moderate for carbohydrates (70.1%), and 96.4% low for fats. Conclusion The prevalence and associated factors among pregnant women who attended the antenatal clinic were revealed, and thus the need for screening and treatment of both high blood pressure and high blood glucose levels. Recommendations: There's a need to advise and sensitize them to complete all the antenatal visits and create awareness among pregnant women.